Optimization of In Vitro Techniques for Distinguishing between Live and Dead Second Stage Juveniles of Heterodera glycines and Meloidogyne incognita - Xiang, Ni; Lawrence, Kathy S. (PloS one, 2016)
Heterodera glycines (Soybean Cyst nematode, or SCN) and Meloidogyne incognita (Root-Knot nematode, or RKN) are two damaging plant-parasitic nematodes on important field crops. Developing a quick method to distinguish between live and dead SCN and RKN second stage juveniles (J2) is vital for high throughput screening of pesticides or biological compounds against SCN and RKN. The in vitro assays were conducted in 96-well plates to determine the optimum chemical stimulus to distinguish between live and dead SCN and RKN J2. Sodium carbonate (Na2CO3), sodium bicarbonate (NaHCO3), and sodium hydroxide (NaOH) were evaluated for the nematode response to see if these compounds can help distinguish between viable from the dead J2. Results indicated that live SCN J2 responded equally (P ≤ 0.05) to 1 μl Na2CO3 and 10 μl NaHCO3 in 100 μl of water at pH = 10. Live SCN J2 responded by twisting their bodies in a curling shape and increasing rate of movements within 2 minutes of exposure. The twisting activity continued for up to 30 minutes. Live RKN J2 responded by increasing activity with the application of 1 μl NaOH in 100 μl of water at pH = 10 also in the 2 minutes to 30 minutes time frame. Furthermore, in growth chamber tests to confirm the infectivity of live SCN. The live SCN as determined by exposure to 1 μl of Na2CO3 indicated 60.5% of the SCN J2 were alive and of those, 29.5% were infective and entered the soybean roots. The 1 μl of NaOH stimulus revealed that 75.2% RKN J2 were alive and of those, 14.9% were infective and entered soybean roots. These results confirmed that 1 μl of Na2CO3 added to 100 μl suspension of SCN J2 and 1 μl of NaOH added to 100 μl suspension of RKN J2 are the effective stimuli for rapidly distinguishing between live and dead SCN and RKN J2 in vitro. SCN and RKN J2 responded differently to different compounds.